2017
DOI: 10.1107/s2059798317009998
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the regulation of chemotaxis by MapZ in the presence of c-di-GMP

Abstract: The bacterial second messenger cyclic diguanylate monophosphate (c-di-GMP) mediates multiple aspects of bacterial physiology through binding to various effectors. In some cases, these effectors are single-domain proteins which only contain a PilZ domain. It remains largely unknown how single-domain PilZ proteins function and regulate their downstream targets. Recently, a single-domain PilZ protein, MapZ (PA4608), was identified to inhibit the activity of the methyltransferase CheR1. Here, crystal structures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Structural superposition of PilZ domains from K. xylinus AcsAB, P. aeruginosa Alg44 and C-terminal domains of E. coli YcgR, V. cholerae PlzD, and K. pneumoniae MrkH against the high-resolution structure of the PilZ domain protein MapZ (PA4608) of P. aeruginosa (24, 26, 40) is shown in Fig. 1, while pairwise superpositions of the domains listed in Table 1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural superposition of PilZ domains from K. xylinus AcsAB, P. aeruginosa Alg44 and C-terminal domains of E. coli YcgR, V. cholerae PlzD, and K. pneumoniae MrkH against the high-resolution structure of the PilZ domain protein MapZ (PA4608) of P. aeruginosa (24, 26, 40) is shown in Fig. 1, while pairwise superpositions of the domains listed in Table 1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, structures of several PilZ domains and PilZ-containing proteins have been solved (22, 24, 25, 34-40), providing valuable insight into the mechanisms of c-di-GMP binding and the roles of the conserved RxxxR and [D/N]xSxxG c-di-GMP-binding motifs (reviewed in ref. 9 and 10).…”
Section: Introductionmentioning
confidence: 99%
“…Within this cluster is MapZ, a single-domain PilZ protein from P. aeruginosa PAO1. MapZ is one of the best characterized PilZ proteins with its structure, interacting partner and physiological function elucidated 5,[31][32][33][34] . In vitro and in vivo studies revealed that MapZ binds c-di-GMP with a KD in the range of 6-9 µM 5, 32 , and that it interacts with the chemotaxis methyltransferase CheR1 at elevated c-di-GMP concentrations.…”
Section: A Large Group Of Single-domain Pilz Proteins Predicted To Inmentioning
confidence: 99%
“…In vitro and in vivo studies revealed that MapZ binds c-di-GMP with a KD in the range of 6-9 µM 5, 32 , and that it interacts with the chemotaxis methyltransferase CheR1 at elevated c-di-GMP concentrations. Crystallographic studies on the MapZ/CheR1/c-di-GMP ternary complex identified that the two C-terminal helices α1 (residues 92-106aa) and α2 (residues 109-121) of MapZ are the key motifs mediating MapZ-CheR1 interaction ( Figure 6C) 7,33 . In particular, the helix α1 plays an essential role in mediating the MapZ-CheR1 interaction by occupying the central cleft of CheR1.…”
Section: A Large Group Of Single-domain Pilz Proteins Predicted To Inmentioning
confidence: 99%
“…Structural superposition of PilZ domains from K. xylinus AcsAB and P. aeruginosa Alg44 and C-terminal domains of E. coli YcgR, V. cholerae PlzD, and K. pneumoniae MrkH against the high-resolution structure of the PilZ domain protein MapZ (PA4608) of P. aeruginosa (24,26,42) is shown in Fig. 1, while pairwise superpositions of the domains listed in Table 1 are shown in Fig.…”
mentioning
confidence: 99%